Relevansi Adat Tikah Kawitn Suku Dayak Barai Kecamatan Kayan Hilir Bagi Perkawinan Gereja Katolik - Siong; Yulius Defri Sudi; Stenly Vianny Pondaag (Sekolah Tinggi Filsafat Seminari Pineleng, 2022)
This paper deals with a marriage ritual of the Dayak Barai tribe, known as Tikah Kawitn. The purpose of this paper is to explore the local wisdom and values behind the marriage customs of the Dayak Barai tribe and to find their relevance for appreciating and living the values of Catholic marriage. This paper uses the Interpretative Phenomenological Analysis (IPA) method. The author finds that the Dayak Barai tribe values the nobility of traditional marriages. It can be seen in pre-wedding rituals and marriage ceremonies designed with symbolic actions. The Tikah Kawitn ritual also contains the essential values of marriage as taught by the Catholic Church, namely monogamy, not being divorced, directed at heredity, and the welfare of the household. The author concludes that the values of the traditional marriage of the Dayak Barai tribe, tikah kawitn, can contribute to the process of deepening and appreciating the nobility of the Catholic Church's marriage, especially for the Dayak Barai tribe who are Catholic.